THE ANTECEDENT AND IMPACT OF GREEN BRAND EQUITY ON HONDA MOTORCYCLE WITH PROGRAMMABLE FUEL INJECTION TECHNOLOGY IN SURABAYA - Michael Saputra Prajugo (Journal of Management and Business, 2015)
This study integrates the research model developed by Ng et al., (2014), Chen (2010), and Bekk et al., (2016) and aims to analyze the antecedent and impact of green brand equity on Honda motorcycle with Programmable Fuel Injection (PGM-FI) technology in Surabaya. A theoretical model with hypothesized relationships is developed consisting of nine latent constructs: perceived quality of a brand, brand credibility, green brand image, green brand perceived value, green satisfaction, green trust, green brand equity, brand attitude, and positive word of mouth communication. The method used to collect the data in this study is distributing questionnaire to 260 respondents who meets the sample characteristics that have been determined. Later, the method used to test the validity and reliability of the data is SPSS 18.0 software and the method used to test the hypotheses is Structural Equation Modeling using Lisrel 8.80 software. The results show that brand credibility, green brand perceived value, and green satisfaction have positive influence on green brand equity, thus having role as the antecedents. On the other hand, green brand image and green trust have no influence on green brand equity. Furthermore, the results show that green brand equity has positive influence on brand attitude and positive word of mouth communication, where the positive influence of green brand equity on positive word of mouth communication can be also through mediation of brand attitude. Thus, brand attitude and positive word of mouth communication are impacts of green brand equity.